Yield of criollo cowpea beans as a function of row spacing and number of plants per hill - Camara, Felipe Thomaz da; Duarte Mota, Antonio Marcos; Araujo Nicolau, Francisca Edcarla de [UNESP]; Pinto, Antonio Alves; Franciele da Silva, Josefa Maria (Univ Estadual Mato Grosso Sul, 2018)
Cowpea beans are one of the main crops in the Northeast region, and it can be cultivated for grain production or in green pods. This article aimed to evaluate the development and yield of cowpea beans in grains and green pods related of the spacing between plants and the practice of thinning in the Cariri region of Ceara State, Brazil. The trial was run at Sitio Pintado in the municipality of Missao Velha, Ceara, Brazil, in a randomized complete block design in a 2x3 factorial scheme, with four replications. The first factor was the spacing between plants (0.50, 0.33 and 0.25 m), and the second was the practice of thinning (with and without thinning). To evaluate the development and yield of green beans, the following variables were analyzed: Plant population, number of pods per plant, the mass of green pods per plant, green mass per pod, and green pods yield. Regarding the variables of bean in grains at 11% moisture, the number of grains per pod, the grain mass per plant, the mass of 100 grains and the grain yield were evaluated. The thinning practice allowed higher values of production per plant, but without improvements in the yield of green beans and pods. For the spacing between the plants, it was observed that the higher yield of grains was for the spacing of 0.4 m, with values of 1,633 kg ha(-1).
Keywords: grains; green pods; plant spacing; thinning